Effect of in-ovo feeding of iron nanoparticles and methionine hydroxy analogue on broilers chickens small intestinal characteristics - Masoumeh Abbasinezhad Laledashti; Ali Asghar Saki; Amir Abbas Rafati; Mansoureh Abdolmaleki (Acta Scientiarum: Animal Sciences, 2020)
The experiment was conducted with 644 Ross fertilized egg by 7 treatments 4 replicates and 23 eggs in each. Seven treatments included two control with and without injection, iron sulfate, iron sulfate nanoparticles, Alimet, Alimet + iron sulfate, Alimet + iron sulfate nanoparticles. After hatching 2 mg iron nanoparticles were applied as new treatment. The highest increased in the intestinal relative weight (p < 0.05) was observed by iron+Alimet in late feeding at day old of age. Also similar trend was found in cecum and duodenum length by iron control 2 and late feeding (18 hours’ after hatching). The highest cecum length was found among all treatments by in ovo injection of iron nanoparticles in early feeding at 21 days of age (p < 0.05). Significantly increased the duodenum length was found by iron sulfate in early feeding at 42 days of age (p < 0.05). In ovo injection of Alimet in late feeding was resulted in decrease jejunum crypt depth at 21 days of age (p < 0.05). The results of this study have shown that the highest jejunum villi width and surface area were recorded in dietary iron sulfate nanoparticles in late feeding at 21 and 42 days of age (p < 0.05).